1995
DOI: 10.1007/bf02254190
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of retinol-binding protein in healthy children and adolescents

Abstract: Retinol-binding protein (RBP) is a marker of tubular reabsorption in the kidneys. The aim of our study was to investigate urinary RBP excretion in healthy children to obtain reference values related to age and pubertal stage. Overnight samples from 143 subjects (73 girls, 70 boys) aged 10-18 years were investigated. RBP was quantified by a solid-phase sandwich enzyme immunoassay. Both the RBP excretion rate and the RBP/creatinine ratio (RBP/Cr) showed a skewed distribution. The medians and the 5th-95th percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…RBP4 is a small molecular weight protein is glomerularly filtrated and, it is reabsorbed by the renal tubular system. Both exceeded tubular capacity and tubular dysfunction could alter RBP4 homeostasis [21, 22]. It has been observed that type 2 diabetic patients have higher urine content of RBP4 [4, 5].…”
Section: Discussionmentioning
confidence: 99%
“…RBP4 is a small molecular weight protein is glomerularly filtrated and, it is reabsorbed by the renal tubular system. Both exceeded tubular capacity and tubular dysfunction could alter RBP4 homeostasis [21, 22]. It has been observed that type 2 diabetic patients have higher urine content of RBP4 [4, 5].…”
Section: Discussionmentioning
confidence: 99%
“…Retinol binding protein (RBP), a low‐molecular‐weight protein, is filtered by the glomeruli and then reabsorbed and catalyzed by the proximal tubules. Increased urinary RBP excretion occurs with altered tubular function and when tubular reabsorptive capacity is exceeded (7). The study was conducted to assess renal tubular function in diabetic patients by measuring urinary excretion of β‐NAG and RBP, and correlating values to DN risk factors such as disease duration, glycemic control, blood pressure, creatinine clearance and urinary albumin excretion (UAE).…”
mentioning
confidence: 99%
“…In agreement with the current study, Bangstad et al . found a similar RBP excretion rate and RBP/Cr ratio in both sexes and linear multiple regression analysis showed no association with age or pubertal stage, although a weak relationship (r = 0.27) was found between RBP excretion rate and age in boys and RBP/Cr ratio and age (r = –0.28) in girls by simple correlation analysis . On the contrary, Lehrnbecher et al .…”
Section: Discussionmentioning
confidence: 85%
“…In agreement with the current study, Bangstad et al found a similar RBP excretion rate and RBP/Cr ratio in both sexes and linear multiple regression analysis showed no association with age or pubertal stage, although a weak relationship (r = 0.27) was found between RBP excretion rate and age in boys and RBP/Cr ratio and age (r = -0.28) in girls by simple correlation analysis. 27 On the contrary, Lehrnbecher et al revealed that urinary levels of RBP showed decreasing levels with increasing age, although no significant correlation was found. 28 Smith et al found a fall in RBP excretion with increasing age particularly in the first year of life.…”
Section: Discussionmentioning
confidence: 95%